Integration of Work Achievement Where Self-Efficacy, Work Interest, Emotional Intelligence and Motivation as Moderating Variables at PT. BNI Medan Branch - Hartoyo, Budi Hartoyo; Chintya Ones Charli; Ariyanto Masnum; Rahmadani Hidayat; Menhard Menhard (Dinasti Publisher, 2023)
This study aims to reveal the effect of integration of work achievement where self-efficacy, work Interest, emotional intelligence and motivation as Moderating variables. This type of research is associative quantitative. The population of this study as many as 151 employees. Sampling using simple random sampling technique as many as 109 respondents. Data analysis using path analysis. The results showed that the variables of work interest and emotional intelligence have a positive and significant effect on job performance through motivation as an intervening variable.